Deteksi Fertilitas Telur Burung Lovebird Berbasis Smartphone - Anugerah Satria Putra Pratama; Mohammad Abdullah Anshori; Hadiwiyatno Hadiwiyatno (Jurnal Jaringan Telekomunikasi, 2021)
Birds are animals that are very much favored by the community. Currently, lovebirds is popular to be kept and even bred, because the cost of maintenance is cheap and the opportunity to raise it is very good and promising. So that many people are interested in pursuing lovebird livestock business even though breeding is neither easy nor difficult. The reseach purpose was to create monitoring system for the quality of lovebird eggs to be declared hatchable and unable to hatch by utilizing conveyor machines, infrared sensors, LDR sensors and servo motors. All these components are connected to smartphone via mcu node. The captured data is sent to firebase and monitored on the smartphone. The data includes the number of fertile and infertile eggs, and the eggs resistance value scanned by the LDR sensor. The system implementation is done by placing sample of lovebird eggs on conveyor machine and then testing it one by one, then the resistance value is displayed on the smartphone, then the average value is calculated, and the percentage of the sensor is successful in reading the egg condition. The results of testing on lovebird eggs produced 2 conditions, fertile and infertilee. If the resistance value is > 505ohm then the egg is declared fertile and it’s declared invert if resistance value is < 505ohm. In distance testing, the most accurate distance is 1-24cm, the sensor cannot work accurately if the distance between eggs shorter, because the sensor takes time to return to the initial scan mode.